The synthesis and complexation study of some novel 3-methoxyphenyl chromenone crown ethers using conductometry - SALAN, ÜMİT (ELSEVIER SCI LTD, 2006)
7,8-Dihydroxy-3-(3,4-dimethoxyphenyl)-2H-chromenoiies, 7,8-diliydroxy-3-(3,5-dimethoxyphenyl)-2H-chromenones and 7,8-dihydroxy-3-(3,4,5-trimethoxypheiiyl)-2H-chromenones, o-diliydroxy-3-iiiethoxyphenyicoumarins, were prepared from 2,3,4-trihydroxybenzaldehyde and corresponding methoxyphenylacetic acid in NaOAc/Ac2O, respectively. 3-Methoxyphenyl-7,8-dihydroxy-2H-chromenone reacted with the polyethylene glycol ditosylate or dichloride in CH3CN/alkali carbonate to afford [12]crown-4, [15]crown-5 and [18]crown-6-chromonones. The chromatographically purified novel chromenone crown ethers were identified with IR, H-1 NMR, 13 C NMR and low and high resolution mass spectroscopy and elemental analysis. Stability constants for the 1:1 complexes of Na+ and K+ with different substituted methoxyphenyl derivatives of coumarino[12]crown-4, coumarino[15]crown-5 and coumarino[18]crowti-6 (5a-5i) have been determined by conductometry at 25 degrees C in a binary solvent, dioxane/water. For all the coumarino crown ether derivatives, the stability constant decreases for K+ ion compared to Na+ ion. The selectivity sequence of these crown ethers in dioxane/water has showed an irregular order with respect to their cavity size. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 3-aryl-chromenone crown ethers; couruarino crown ethers; synthesis; complexation; binary solvent; conductometry; COUMARIN DERIVATIVES; CATION-BINDING; ION-PAIR; CU(II); SODIUM; ZN(II); NI(II)